Should doctors tackling covid-19 be immune from negligence liability claims?. (1st July 2020) - Tomkins, Christine; Purshouse, Craig; Heywood, Rob; Miola, José; Cave, Emma; Devaney, Sarah
Abstract : Litigation related to exceptional circumstances would be a complicated drain on a workforce and system already on its knees after the pandemic, says Christine Tomkins . But Craig Purshouse, Rob Heywood, José Miola, Emma Cave, and Sarah Devaney argue that, despite extraordinary times, immunity from negligence is unnecessary and sends the wrong message about practice standards